BagaimanaPersepsi, Pengetahuan dan Perilaku Petugas Terhadap Pelaporan Kejadian Phlebitis di Instalasi Rawat Inap RS X? - Rahmanita Yusman; Nurwulan Andadari; Yetty Nusaria (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2017)
Infection prevention and control program is one measure of the quality of services that must be performed in a hospital. Phlebitis is one of nosocomial infection that occur in hospitals,, The sign of Phlebitis include with pain, redness, palpable soft, swelling, and feels hot on the location of the puncture. In preliminary studies showed the incidence of phlebitis and incidence of phlebitis registration numbers are still below standard. Objective of this study was to determine the root cause of the high incidence of phlebitis in terms of recording and reporting system the incidence of phlebitis. This was a quantitative descriptive study were obtained throught qustionnaire-base and interview is conducted to 12 respondents who consist of 5 nurses, 5 IPCLN (Infection Prevention and Control Link Nurse)and 2 head room. The results showed among of 91,7% of respondents state that the sign of Phlebitis that reported was if there are 3 signs, among of 66,7% of respondents agreed that making the report will takes too musch time and embroider jobs, among of 41,7% of respondents agreed that there are reward in any kind to reporting is conducted. The root cause of a less than optimal for recording and reporting the incidence of phlebitis were nurses do not understand how filling the form survailens, nurses procrastinator forget to fill and take survailens form of medical record documents and agreed to do the phlebitis criteria for recording and reporting. To disseminate the importance of recording and reporting, dissemination phlebitis criteria approved hospital and re-socialization of recording and reporting procedures phlebitis survailens recommended to reduce the incidence of phlebitis and improve the accuracy of the data recording and reporting the incidence of phlebitis.